Macroeconomic Determinants And Greenium In Indonesian Green Sukuk: A Systematic Literature Review - Muhammad Rijal Alim Rahmat; Rahmat Burhamzah (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
Greenium (green premium) is a critical indicator for assessing the efficiency of environmentally oriented financing in the Islamic capital market. However, the sensitivity of this instrument to macroeconomic shocks, particularly the Jakarta Composite Index (IHSG) and the exchange rate, remains mixed in the empirical literature. This study aims to comprehensively map the scientific consensus on the influence of macroeconomic variables on the price performance of green sukuk and the formation of the greenium component in Indonesia. Using a systematic literature review (SLR) structured according to the PRISMA protocol, 10 relevant scientific articles from reputable databases were analyzed in depth. The review indicates a strong consensus that, in the short run, the IHSG exerts a negative effect on instrument returns through portfolio rotation between equities and sukuk. By contrast, rupiah depreciation has a positive long-run effect by raising secondary-market yields as compensation for higher currency risk. Nevertheless, a substantial research gap remains: no direct empirical evidence has yet tested the relationship between stock market volatility and the greenium component (yield spread) specifically in the domestic market; the available evidence is limited to instrument price performance alone. The policy implications point to the need for restructuring fiscal and tax incentives and differentiating marketing strategies according to retail and institutional investor segments in order to preserve the stability of the sustainable financial market.